A molecular phylogeny recovers Strabomantis aramunha Cassimiro, Verdade and Rodrigues, 2008 and Haddadus binotatus (Spix, 1824) (Anura: Terrarana) as sister taxa - Amaro, Renata C. (2013)
The taxonomic and biogeographic affinities of Strabomantis aramunha from the Campos Rupestres of Brazil are intriguing. A unique skull morphology of females suggest affinities with the broad-headed eleutherodactylines of Northwestern South America in the genus Strabomantis. Male and juvenile morphology nonetheless suggest S. aramunha could be related to members of the recently described genus Haddadus from eastern Brazil. We assess the affinities of S. aramunha using molecular phylogenetic analyses of mitochondrial (12S, tRNAval, 16S, cyt b) and nuclear sequences (RAG-1and rhodopsin). Bayesian inference, likelihood, and parsimony analysis recover a highly supported clade with S. aramunha and H. binotatus as sister taxa. Accordingly, we transfer S. aramunha to Haddadus, and provide a new generic definition of the later. The distribution of species in Haddadus (highlands of the Espinhaço mountain Range and coastal eastern Brazil) is now concordant with the general pattern observed for other species in the area. © 2013 Magnolia Press.